Occupational exposure to dust in road construction, earthworks and open-pit mining – a scoping review protocol - J. Duarte; Mário Vaz; J. Torres Costa; J. Santos Baptista (International Journal of Occupational and Environment Safety, 2019)
The exposure to respirable particulates poses a significant threat to human health globally. Several occupational activities can contribute to this problem, being open-pit mining and related activities such as road construction and earthworks some examples. This systematic review protocol outlines the main procedures to conduct a scoping review which aims to identify the most adequate variables to plan safety since the design safe. To accomplish this primary objective, some secondary objectives were defined as well. The journals and databases considered more relevant were selected (i.e. Scopus, Web of Science, and Science Direct) and a set of keywords was defined to the latter sequenced combination. The selection process of the articles is also described, in an attempt to contribute to further research on this field. Every methodology is documented and supported by the PRISMA Statement adapted to the scoping review process. All of the data treatment is detailed, including the risk of bias and attempts to manage it.